2015
DOI: 10.5005/jp-journals-10018-1154
|View full text |Cite
|
Sign up to set email alerts
|

New Cutoff Point for Platelet Count/Spleen Diameter Ratio to Predict Esophageal Varices in Patients with Hepatitis C Virus-related Hepatic Cirrhosis

Abstract: The esophagogastroduodenoscopy (EGD) with all its hazards remains the gold standard screening tool for esophageal varices. Noninvasive tools have been proposed and studied to replace the EGD. Platelet count (PC)/spleen diameter (SD) ratio as a noninvasive tool for predicting the presence of esophageal varices was proposed and studied in many previous studies.How to cite this articleEl-Sherbiny W, Elegezy M, Shaltout SW. New Cutoff Point for Platelet Count/ Spleen Diameter Ratio to Predict Esophageal Varices in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous studies have reported a correlation between the platelet count, spleen size, and EGV in patients with cirrhosis (14)(15)(16)(17)(18)(19). The platelet count/spleen length ratio or platelet count/spleen diameter ratio has been validated to stratify the risk of EGV and can be used as a triage test before endoscopy to exclude adults without varices (20).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a correlation between the platelet count, spleen size, and EGV in patients with cirrhosis (14)(15)(16)(17)(18)(19). The platelet count/spleen length ratio or platelet count/spleen diameter ratio has been validated to stratify the risk of EGV and can be used as a triage test before endoscopy to exclude adults without varices (20).…”
Section: Introductionmentioning
confidence: 99%